Membrane Supported Virus Separation from Biological Solutions. Issue 8 (14th June 2013) - Grein, Tanja A.; Kovacs, Zoltan; Ebrahimi, Mehrdad; Michalsky, Ronald; Czermak, Peter; Wessling, Matthias
Abstract Industrial production of cell culture‐derived viruses or virus‐like particles for gene therapy or as expression systems for vaccine production is a complex multi‐step process. Unfortunately, process intensification and optimization efforts mostly focus on increased reactor yields, neglecting the potential for materials design and process development for downstream unit operations that often are the bottleneck of a biopharmaceutical manufacturing process. Membrane‐based virus filtration represents an economical trade‐off towards biotechnological downstream processing with moderate to high yields and purity on one hand and relative fast process kinetics, and thereby reduced equipment size and costs, on the other hand. This article provides a short review of recent development and applications of membrane materials and membrane‐based unit operations for virus separation in the manufacturing trains of vaccines or viral vectors for gene therapy.